Neglected Coats Disease: Determining the Most Appropriate Treatment: Poster Presentation - Case Report - Resident - Anastasia, Ruth; Yustiarini, Ima; Prakosa, Ady Dwi; Widjaja, Sauli Ari; Firmansjah, Muhammad; Sasono, Wimbo (Majalah Oftalmologi Indonesia, 2023)
Introduction : Coats disease is defined as retinal telangiectasia and aneurysm with retinal exudation that typically found in unilateral eyes of young male. This condition remains a diagnostic challenge because of its varied presentation. Case Illustration : A 12-years-old boy presented with a chief complaints of vision loss and pain in the right eye in the last 3 months and gradually blurred vision for a year. Visual acuity was positive light perception in the right eye and 5/5 in the left eye. Intraocular pressure of the right eye was 43.4 mmHg and 15mmHg of the left eye. Slit lamp examination of the right eye revealed conjunctival hyperemia, slightly corneal oedema, iris neovascularization, xantocoria, dilated pupil. Bullous total exudative retinal detachment with telangiectasia in all quadrants was found in the ophthalmoscopy examination of the right eye and left eye is within normal limit. The patient was diagnosed with stage IV coats disease and antiglaucoma agents was given as initial treatment. Discussion : Coats disease is a clinical diagnosis that can be assessed by clinical triad of exudative retinal detachment, irregularly-dilated telangiectatic vessel, and peripheral nonperfusion and can be supported by the diagnostic tools such as Ultrasonography, OCT, CT-Scan and MRI. Treatment of coats disease varies depend on the stage. In stage IV coats disease, external drainage is the most appropriate treatment. The more advanced stages demonstrating poor visual acuity both at presentation and at the time of final visit Conclusion : Majority of coats disease cases present with advanced stage therefore cause limited treatment option and poorer prognosis.